Chitosan-encapsulated manganese ferrite particles bearing sulfonic acid group catalyzed efficient synthesis of spiro indenoquinoxalines. Issue 55 (9th September 2020) - Lahouti, Sepideh; Naeimi, Hossein
Abstract : A simply, highly versatile and efficient synthesis of 5-phenyl-spiro [diindeno pyridineindenoquinoxaline]-diones is achieved through five component one pot reaction of ninhydrin, 1, 2-diaminobenzene, 1, 3-indandione and anilines. Abstract : A simple, highly versatile and efficient synthesis of 5-phenyl-spiro[diindenopyridine-indenoquinoxaline]-diones is achieved through a four-component one pot reaction of ninhydrin, 1, 2-diaminobenzene, 1, 3-indandione and aniline. This reaction was catalyzed by MnFe2 O4 @CS-Bu-SO3 H MNPs as a very efficient, recyclable heterogeneous catalyst in acetonitrile under reflux conditions. The catalyst can be recovered from the subsequent reaction mixture and reused for at least five cycles without any appreciable loss in its efficiency. The core–shell structure and composition of the produced magnetic nanocatalyst were analyzed using FT-IR, XRD, VSM, SEM, EDX and TGA techniques.